2022
DOI: 10.3389/fendo.2022.799337
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chinese Patent Medicines on Ocular Fundus Signs and Vision in Calcium Dobesilate-Treated Persons With Non-Proliferative Diabetic Retinopathy: A Systematic Review and Meta-Analysis

Abstract: BackgroundDiabetic retinopathy (DR), one of the commonest microvascular complications in diabetic patients, is featured by a series of fundus lesions. Conventional Western medicine therapies for DR are always with modest treatment outcome. This paper is to assess the ocular fundus signs, vision and safety of Chinese patent medicines (CPMs) as an add-on treatment for DR.Method7 electronic databases were searched to determine eligible trials. Randomized controlled trials (RCTs) of non-proliferative diabetic reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…This NMA systematically evaluated the efficacy and safety of 7 commonly used OCPMs (CXC, CDDP, QG, SDMUC, MMDHP, HXMMT, and DHHYK) alone or combined with CD in patients with NPDR based on information from 42 studies involving 7 categories of outcomes. Our results showed that OCPMs alone or combined with CD were superior to CD alone in terms of an improved clinical efficacy rate, improved visual acuity and visual field gray value, reduced fundus hemorrhage and exudation, and better drug safety, which is consistent with the results of a published pairwise meta-analysis ( 11 ). More so, by comparing different types of proprietary Chinese medicines, the NMA also suggests that more attention should be given to CDDP, CXC, HXMMT, and SDMMC in the clinical treatment of NPDR.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This NMA systematically evaluated the efficacy and safety of 7 commonly used OCPMs (CXC, CDDP, QG, SDMUC, MMDHP, HXMMT, and DHHYK) alone or combined with CD in patients with NPDR based on information from 42 studies involving 7 categories of outcomes. Our results showed that OCPMs alone or combined with CD were superior to CD alone in terms of an improved clinical efficacy rate, improved visual acuity and visual field gray value, reduced fundus hemorrhage and exudation, and better drug safety, which is consistent with the results of a published pairwise meta-analysis ( 11 ). More so, by comparing different types of proprietary Chinese medicines, the NMA also suggests that more attention should be given to CDDP, CXC, HXMMT, and SDMMC in the clinical treatment of NPDR.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, early treatment and prevention at the stage of NPDR have become an urgent clinical problem to be solved. In China, clinicians often apply OCPMs for the treatment of NPDR with good clinical efficacy ( 11 ). DR belongs to the category of “thirsty eye disease” according to traditional Chinese medicine, and its pathogenesis is mainly attributed to the deficiency of both qi and yin and the stasis of ocular collateral ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous meta‐analyses have demonstrated that the Chinese patent medicines (including Compound Danshen Dripping Pills, Compound Xueshuantong Capsule, Qiming granule) as an add‐on therapy for diabetic retinopathy have additional benefits and are generally safe. Chinese patent medicines combined with calcium dobesilate could improve retinal microaneurysm, hemorrhage, macular thickness, visual acuity, fasting blood glucose, and HbA1c compared with calcium dobesilate alone 25 . Another network meta‐analysis that included 41 RCTs found that the treatment plan of Dihuang pill prescriptions combined with conventional treatment could reduce serum creatinine, 24‐h urinary protein, and fasting blood glucose urine protein excretion rate and improve the total clinical effective rate; the combination of medicine was obviously better than conventional medicine alone 26 .…”
Section: Utilizing Tcm Management Techniques To Prevent or Relieve Co...mentioning
confidence: 97%
“…Chinese patent medicines combined with calcium dobesilate could improve retinal microaneurysm, hemorrhage, macular thickness, visual acuity, fasting blood glucose, and HbA1c compared with calcium dobesilate alone. 25 Another network meta‐analysis that included 41 RCTs found that the treatment plan of Dihuang pill prescriptions combined with conventional treatment could reduce serum creatinine, 24‐h urinary protein, and fasting blood glucose urine protein excretion rate and improve the total clinical effective rate; the combination of medicine was obviously better than conventional medicine alone. 26 As for TCM foot baths and acupoint massages, they may promote microcirculation, enhance skin permeability, and increase drug absorption.…”
Section: Utilizing Tcm Management Techniques To Pr...mentioning
confidence: 99%